2009
DOI: 10.1007/s11626-009-9191-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of signaling pathways in bovine sperm motility, and effect of ergot alkaloids

Abstract: There is evidence that ergot alkaloids can directly interact with mammalian spermatozoa affecting sperm functions. Ergot alkaloids exert their toxic or pharmaceutical effects through membrane receptor-mediated activities. This study investigated the signaling pathways involved in the in vitro inhibitory effects of both ergotamine (ET) and dihydroergotamine (DEHT) on the relative motility of bovine spermatozoa using specific inhibitors. Motile bovine spermatozoa were prepared using a Percoll gradient and incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Ergotamine and dihydroergotamine reportedly inhibited sperm motility in a dosedependent manner (Wang et al, 2009), and ergotamine tartrate decreased the ability of sperm to fertilize bovine oocytes (Schuenemann et al, 2005c). Wang et al (2009) suggested that ergotamine and dihydroergotamine decreased the percentage of motile bovine spermatozoa via a-adrenergic receptors with G-protein signaling pathways, with cAMP and intracellular calcium having a passive role in altering sperm motility. Whole animal studies investigating ergot alkaloid effects on sperm characteristics have been less decisive than in vitro research.…”
Section: Reproductivementioning
confidence: 99%
“…Ergotamine and dihydroergotamine reportedly inhibited sperm motility in a dosedependent manner (Wang et al, 2009), and ergotamine tartrate decreased the ability of sperm to fertilize bovine oocytes (Schuenemann et al, 2005c). Wang et al (2009) suggested that ergotamine and dihydroergotamine decreased the percentage of motile bovine spermatozoa via a-adrenergic receptors with G-protein signaling pathways, with cAMP and intracellular calcium having a passive role in altering sperm motility. Whole animal studies investigating ergot alkaloid effects on sperm characteristics have been less decisive than in vitro research.…”
Section: Reproductivementioning
confidence: 99%
“…Tall fescue toxicosis is usually more detrimental to animal performance during extreme temperatures (15). It appears from our animal study (13), as well as the laboratory experiment (24), sperm motility is reduced when exposed to ergot alkaloids commonly found in toxic tall fescue plants. The general rule is 1 bull for 20 to 25 cows during the breeding season.…”
Section: Effects Of Toxic Tall Fescue On Bull Reproductive Performancementioning
confidence: 99%
“…Clinically, chilled and frozen sperm cells would be more fragile and less fertile. Toxic ergot alkaloids can induce motility changes in bull sperm cells through alpha‐adrenergic receptors (Wang et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The reported fiscal impact of ergot alkaloids is in the tens and hundreds of millions of dollars. The greatest clinical and financial impact is in the beef industry, with cattle being affected with a number of pathologies (Burfening 1973;Peters et al 1992;Porter and Thompson 1992;Aldrich et al 1993;Dyer 1993;Porter 1993;Hill et al 1994Hill et al , 2000Oliver et al 1994;Cheeke 1995;Schneider et al 1996;Stuedemann et al 1998;Schultze et al 1999;Schnitzius et al 2001;Parish et al 2003;Matthews et al 2005;Realini et al 2005;Wang et al 2009). The symptoms in cattle include increased respiration rates, increased rectal temperatures, salivation, nervousness and rough hair coats, decreased weight gains and decreased overall performance in beef steers (Hoveland 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation